Antimicrobial Activity of Acacia Nilotica and Ziziphus Mauritiana against Clinical Isolates of Escherichia Coli and Klebsiella Aerogenes - Usman, A.; Ahmad, M.; Hamza, M. M.; Hussaini I. M.; Sanusi, S. B.; Innocent, A. A (UMYU Journal of Microbiology Research)
Klebsiella aerogenes is an opportunistic pathogen linked to several nosocomial illnesses, including pneumonia, sepsis, and infection of the urinary tract. Escherichia coli is frequently the source of numerous common bacterial illnesses, including bacteraemia, cholecystitis, cholangitis, urinary tract infections (UTI), traveler's diarrhoea, and other medical conditions such as meningitis in babies and pneumonia. This study aimed at determining the antimicrobial activity of Acacia nilotica and Ziziphus mauritania on clinical isolate of E. coli and K. aerogenes. The phytochemical constituents of Z. mauritiana and A. nilotica were determined. E. coli and K. aerogenes isolates were obtained from the Barau Dikko Teaching Hospital, Kaduna and reconfirmed using standard microbiological techniques. The antibacterial activity of Z. mauritiana and A. nilotica extracts against the isolates was determined using Agar well diffusion assay, the MIC and MBC was also determined and recorded. The findings of this study revealed that tannins, quinone, phenols, terpenoids, and steroids are present in Z. mauritiana extract while tannins, saponin, quinones, and terpenoids in A. nilotica extract. There was no activity of Z. mauritiana against any of the test isolates at all concentrations used in this study. Whereas A. nilotica exhibited an antibacterial activity against both E. coli and K. aerogenes recording respectively a zone of inhibition of 24 mm and 25 mm with MIC and MBC value of 600 mg/ml. This research displayed an antibacterial activity of A. nilotica and no activity of Z. mauritiana against E. coli and K. aerogenes.